Short-term deformational analysis of prestressed concrete beams using flexural constitutive model - Zamblauskaitė, Renata; Kaklauskas, Gintaris; Bačinskas, Darius; Christiansen, Morten Bo (Journal of Civil Engineering and Management, 2003)
In this paper, an attempt has been made to extend application of the recently proposed Flexural constitutive model to short-term deformational analysis of flexural prestressed concrete members. The relationship of tensile concrete is based on smeared crack approach and accumulates cracking and the tension stiffening effects. The Flexural constitutive model was applied in a simple engineering technique based on principles of strength of materials and the layered approach. To assess accuracy of the technique, deflections have been calculated for experimental prestressed concrete beams reported in the literature. Comparison has been earned out with the predictions of the well-known design code methods of different countries.First Published Online: 26 Jul 2012